Kualitas Pelayanan dan Pengaruhnya terhadap Minat Kunjungan Ulang Pasien Rawat Jalan pada Poliklinik Dirumah Sakit Islam Faisal Makassar - Shulystiawaty Desy Resky; Anggung Dinianti; Irwan Irwan (Journal of Educational Innovation and Public Health, 2025)
Faisal Islamic Hospital Makassar currently has good service quality on the interest in repeat visits to outpatients in polyclinics with an increasing number of outpatient visits. However, there are also services that are desired by patients and families of patients so that the service is said to be bad. This is felt by patients visiting the hospital, namely the better the services provided where before the researchers conducted the research there were still many shortcomings in the form of medical devices and irregular service hours. Where the quality of service can also be said to be good if the service provided is in accordance with what the patient wants and can be said to be satisfactory service. Therefore, to increase the number of patient visits, the hospital tries to provide quality service so that patients feel satisfied. Revisit interest is the behavior that occurs in response to a service that shows the customer's desire to revisit the hospital. This study aims to determine the quality of service and its effect on outpatient revisit interest in polyclinics at Faisal Makassar Islamic Hospital. The population in this study was 750 patients and the sample size was 254 patients who made a repeat visit at the polyclinic of the Faisal Islamic Hospital Makassar. The results of this study are the level of repeat visits on an outpatient basis at the Faisal Makassar Islamic Hospital can be seen from the aspects of tangible (physical evidence) of good value, reliability (reliability) of good value, responsiveness (responsiveness) of good value, assurance (certainty) of good value, and empathy (empathy) of good value.